Impact of coronary artery bypass grafting in elderly patients - Aikawa,Priscila (2013)
OBJECTIVE: To analyze the results of isolated on-pump coronary artery bypass graft surgery (CABG) in patients > 65 years-old. METHODS: Patients undergoing isolated on-pump CABG from December 1st 2010 to July 31th 2012 were divided in two groups: GE (elderly > 65 years-old, n=103) and GA (adults < 65 years-old, n=150). Preoperative data, intraoperative (as cardiopulmonar bypass time, aortic clamping time, time length of stay in mechanical ventilation - MV - and number of grafts), and postoperative variable (as morbidity, mortality and time length of stay in hospital) were analyzed during hospitalization. RESULTS: In GE, the morbidity rate was greater than in GA (30% vs. 14%, P=0.004), but there was no difference in the mortality rate (5.8% vs. 2.0%, P=0.165). In GA, there was higher prevalence DM (39.6% vs. 27%, P=0.043) and smoking (32.2% versus 19.8%, P=0.042); and in GE, higher prevalence of stroke (17% vs. 6.7%, P=0.013). There was no difference between the groups regarding intraoperative variables. After multivariate analysis, age > 65-year-old was associated with greater morbidity, but it was not independent predictive factor for in-hospital mortality. Considering in-hospital mortality, stay in ward time length (P=0.006), cardiac (P=0.011) and respiratory complications (P=0.026) were independent predictive factors. CONCLUSION: This study suggests that patients > 65-year old were at increased risk of postoperative complications when submitted to isolated on-pump CABG in comparison to patients < 65-year-old, but not under increased risk of death.